Dendritic sulfonated polyethersulfone nanofiber membrane@LaCoO3 nanowire-based composite solid electrolytes with facilitated ion transport channels for high-performance all-solid-state lithium metal batteries. Issue 6 (17th January 2023) - Yang, Qi; Deng, Nanping; Zhao, Yixia; Gao, Lu; Liu, Weicui; Liu, Yarong; Cheng, Bowen; Kang, Weimin
Abstract : This work provides a composite solid electrolyte combining dendritic SPES nanofibers and LaCoO3 nanowires for ASSLIBs. Benefitting from the promotion of electrolytes on rapid ion deposition, the pouch cell possesses excellent cycle performance. Abstract : All-solid-state electrolytes are widely used in lithium metal batteries of high energy density with assured safety. However, the poor mechanical strength and low ionic conductivity of polymer electrolytes at room temperature hinder their fast development and application in all-solid-state lithium metal batteries. In this study, a rigid and flexible composite solid electrolyte (CSE), with eminent mechanical strength and high ionic conductivity, combining a dendritic sulfonated polyethersulfone (SPES) nanofiber membrane with lanthanum cobaltate (LaCoO3 ) nanowires was developed. The LaCoO3 nanowires present some merits such as their own oxygen vacancies and Lewis acid sites, which can greatly adsorb anions. Meanwhile, the designed 3D structure can also provide the effective contact interface with PEO, which allows more Li + to be transported along the interface of nanofibers and the organic–inorganic interface transportation. The firmly dendritic SPES fiber not only creates an amorphous area similar to a cross traffic network in the PEO, but also provides high mechanical properties for the CSE. Therefore, the fabricated CSE exhibits an excellent ionic conductivity of 1.86 × 10 −4 S cm −1 at 30 °C, an outstanding ion transference number of 0.58 and a good mechanical strength of 6.3 MPa. In addition, the assembled Li/Li symmetrical battery with the CSE can circulate 1400 h at 0.2 mA h cm −2 . Moreover, the obtained CSE exhibits excellent compatibility with LiFePO4 and high-voltage LiNi0.8 Mn0.1 Co0.1 O2 (NMC811) electrodes. Even when the CSE is assembled with LiFePO4 /Li and NMC811/Li into a pouch cell, an initial capacity of 143.9 mA h g −1 can be obtained in the assembled LiFePO4 /Li pouch cell, and the NMC811/Li pouch cell possesses a high specific capacity of 183.69 mA h g −1 . The research will provide a new direction for developing a rigid and flexible solid electrolyte.